"Rafting on the Martha Brae" - Penrod, John (Kingston : The Novelty Trading Co.)
Postcard showing rafters rafting with a group of tourist on the Martha Brae River in Falmouth.
Keywords: Postcards -- Jamaica; Rafts; Martha Brae (Falmouth, Jamaica); Rivers -- Jamaica; Tourism -- Jamaica; Tourists